Analisis Keberlanjutan Hutan Kemasyarakatan Berbasis Agroforestri Kopi di Kawasan Hutan Lindung Bukit Daun Kabupaten Rejang Lebong Provinsi Bengkulu - Korenia Putri Nadia; Septri Widiono; Lathifah Khairani; Rizka Amalia Nugraha (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
ABSTRACTCoffee agroforestry-based Community Forest (HKm) management in the Bukit Daun Protected Forest Area, Rejang Lebong Regency, represents a strategic approach to sustaining forest resources while enhancing community livelihoods. The sustainability of this management system is shaped by five key dimensions: social, ecological, economic, technological, and institutional. This study evaluates sustainability levels using the Complex Proportional Assessment (COPRAS) method and pinpoints the most influential indicators through Principal Component Analysis (PCA). Primary data were collected from 96 coffee farmers belonging to five Gapoktan (farmer groups) across five villages. Findings reveal that all Gapoktan demonstrate a high degree of sustainability. The most dominant sustainability indicators identified are: awareness of rights, participation, technical knowledge, and engagement in activities beyond the HKm permit (social); biodiversity and soil health (ecological); business efficiency (economic); adoption of technology (technological); and effective group management, social values as a binding force among members, and local wisdom (institutional).